Comparison of NT-proBNP levels in hemodialysis versus peritoneal dialysis patients - Ludka, Ondrej; Spinar, Jindrich; Tomandl, Josef; Konecny, Tomas (Biomedical papers, 2013)
Background: Plasma N-terminal fragment of pro brain natriuretic peptide (NT-proBNP) concentration is elevated in cardiovascular diseases such as congestive heart failure, where increased levels of NT-proBNP indicate cardiac dysfunction, hypervolemia, and higher risk of hospitalization and death. These associations apply also to patients with severe impairment of kidney function. Little is known about diferences in plasma level of NT-proBNP in patients receiving hemodialysis (HD) versus those receiving continuous ambulatory peritoneal dialysis (CAPD).Aim: To evaluate differences in plasma NT-proBNP concentration between HD and CAPD patients.Methods: Plasma NT-proBNP concentration was prospectively measured in consecutive patients receiving either HD or CAPD at our hospital center. All other standard clinical parameters were recorded. The correlation between plasma NT-proBNP concentration and the type of dialysis was then examined.Results: We studied 99 consecutive patients on HD (age 62 ± 15 years, 66% male) and 18 consecutive patients on CAPD (age 56 ± 18 years, 67% male). Both groups had similar baseline characteristics including duration of dialysis, left ventricular function and mass, and cardiothoracic ratio. Significantly more patients on HD had abnormal NT-proBNP levels compared to patients on CAPD (97% vs 44%; P
Keywords: hemodialysis; continuous ambulatory peritoneal dialysis; NT-proBNP; ejection fraction